Investigation of radiation protective features of azadispiro derivatives and their genotoxic potential with Ames/Salmonella test system - Alaylar, Burak; Aygun, Bunyamin; Turhan, Kadir; Karadayi, Mehmet; Cinan, Esra; Turgut, Zuhal; Karadayi, Gokce; Abu Al-Sayyed, Mohammed Ibrahim; Gulluce, Medine; Karabulut, Abdulhalik (TAYLOR & FRANCIS LTD, 2023)
Purpose Five different types of synthesized azadispiro derivatives have been analyzed for radiation absorption capacity and determined their potential to be exploited as substances for a drug to be developed against radiation has been investigated. Material and methods Fast neutron attenuation parameters like the effective mean free path, half-value layer (HVL), removal cross-sections, and neutron transmission number were found with the Monte Carlo simulation Geometry And Tracking (GEANT4) code. Gamma radiation absorption parameters, such as effective atom number (Z(eff)), mean free path (MFP), mass attenuation coefficient (MAC), and half-value layer (HVL) were theoretically determined with WinXCom software. Besides, the exposure build-up factor (EBF) was calculated by using GP fitting parameters. Neutron absorption dose rate was experimentally calculated with Am-241-Be fast neutron source which has 4.5 MeV of energy, 74 GBq activity, and portative BF3 neutron detector. Ames/Salmonella test systems were used for the genotoxic potentials of the azadispiro derivatives Results and conclusions Experimental and theoretical results were checked with paraffin and High-Density Polyethylene. The results showed that Azadispiro derivatives have neutron radiation absorption capability close to paraffin and High-Density Polyethylene. The gamma radiation absorption properties for azadispiro derivatives have been investigated, and it has been observed that these materials can absorb gamma radiation. Ames/Salmonella assay was used to examine whether the derivatives had a genotoxic effect probability or not. The results showed that these derivatives were genotoxic and safe at test doses (up to 5 mM). Consequently, it has been understood that these azadispiro derivatives can be used as active and genotoxic safety ingredients in the production of a protective drug against both neutrons and gamma rays.
Keywords: Azadispiro derivatives; radiation; genotoxicity; Ames test system; drugs; EXPOSURE BUILDUP FACTORS; GAMMA-RAY; COMPOSITE-MATERIALS; SPIRO-DERIVATIVES; DESIGN; PARAMETERS; SCATTERING; GLASSES; Life Sciences & Biomedicine - Other Topics; Nuclear Science & Technology; Radiology, Nuclear Medicine & Medical Imaging